Pengantar studi Al-Quran / Abdullah Saeed; penerjemah, Shulkhah, Sahiron Syamsuddin; editor, M. Nur Prabowo S., Fejrian Yazdajird Iwanebel - Saeed, Abdullah ; Shulkhah ; Sahiron Syamsuddin ; Nur Prabowo S., M. ; Fejrian Yazdajird Iwanebel (Baitul Hikmah Press, 2018)
xii, 363 halaman ; 23 cm